2012
DOI: 10.4103/0973-029x.98502
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human herpes viruses in patients with chronic and aggressive periodontitis and relationship between viruses and clinical parameters

Abstract: Background and Aims:Recent microbiological researches have revealed the possible role of human cytomegalovirus (HCMV), Epstein barr virus (EBV), and herpes simplex virus (HSV-1 and HSV-2) in the etiopathogenesis of periodontal diseases. The present pilot study has been undertaken to detect the presence of these viruses in chronic periodontitis, aggressive periodontitis, and healthy individuals and to determine the relationship between these viruses and the clinical parameters.Materials and Methods:A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 21 publications
1
62
4
1
Order By: Relevance
“…The possible reason why these same results were not found in our study are the age range, ethnic differences, the limited sample size, the methodology used, and the probable stage of herpes virus latency. Das et al (2012) carried out a study to detect the presence of human cytomegalovirus (HCMV), Epstein barr virus (EBV), and herpes simplex virus (HSV-1 and HSV-2) in chronic periodontitis, aggressive periodontitis, and healthy individuals divided into three groups: periodontally healthy individuals aged ≥ 21 years -45 years with a sulcus depth ≤ 3 mm; chronic periodontitis in patients aged ≥ 35 years, with 30% of sites involved, a periodontal pocket depth ≥ 6 mm, and an attachment loss ≥ 3 mm, with severe bone loss (≥50% of root length) and patients with aggressive periodontitis aged ≥ 18 years, with 30% of sites involved, a periodontal pocket depth ≥ 6 mm, and an attachment loss ≥ 3 mm, with severe bone loss (≥50% of root length). In these patients HSV-1 was detected in sites with chronic periodontitis in 76% in sites with aggressive periodontitis in 80%; EBV was detected in 32% of sites of chronic periodontitis and aggressive periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The possible reason why these same results were not found in our study are the age range, ethnic differences, the limited sample size, the methodology used, and the probable stage of herpes virus latency. Das et al (2012) carried out a study to detect the presence of human cytomegalovirus (HCMV), Epstein barr virus (EBV), and herpes simplex virus (HSV-1 and HSV-2) in chronic periodontitis, aggressive periodontitis, and healthy individuals divided into three groups: periodontally healthy individuals aged ≥ 21 years -45 years with a sulcus depth ≤ 3 mm; chronic periodontitis in patients aged ≥ 35 years, with 30% of sites involved, a periodontal pocket depth ≥ 6 mm, and an attachment loss ≥ 3 mm, with severe bone loss (≥50% of root length) and patients with aggressive periodontitis aged ≥ 18 years, with 30% of sites involved, a periodontal pocket depth ≥ 6 mm, and an attachment loss ≥ 3 mm, with severe bone loss (≥50% of root length). In these patients HSV-1 was detected in sites with chronic periodontitis in 76% in sites with aggressive periodontitis in 80%; EBV was detected in 32% of sites of chronic periodontitis and aggressive periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the herpesviruses, herpes simplex 1 and 2 (HSV-1, HSV-2) are common causes of infection (Chayavichitsilp et al, 2009). Some studies have found a relationship between these subspecies and periodontal disease (Das et al, 2012). Other studies have found these subspecies both in patients with periodontal disease and in periodontally healthy patients, although HSV was more frequent in periodontitis lesions (Contreras et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with aggressive periodontitis, the microbial load of P. intermedia correlates with the loss of the level of clinical attachment. [26] In vitro demonstrated that P. intermedia LPS causes expression of pro-inflammatory cytokines by gingival epitheliocytes of a gum and human periodontal ligament cells. [27] C. rectus…”
Section: P Intermediamentioning
confidence: 99%